Effects of interventions for women and their partners to reduce or prevent stress and anxiety: A systematic review - Hayes, Catherine (Elsevier/Australian College of Midwives (ACM), 2020)
Background: The period from conception to two years postpartum (the first 1000 days) represents a normative transitional period, which can be potentially stressful for some parents. Parental stress and anxiety adversely impacts psychological and physical health for parents and children. Aim: The aim of this review is to systematically examine effects of interventions for women and their partners to reduce or prevent stress and/or anxiety during the first 1000 days. Methods: MEDLINE, Embase, CINAHL, PsychINFO, and Maternity and Infant Care were searched from inception to March 2019. Randomised controlled trials examining intervention effects on parental stress and/or anxiety during first 1000 days were eligible for inclusion. Data were independently extracted by two reviewers and narratively synthesised. Findings: Fifteen interventions, reported in 16 studies, met inclusion criteria (n = 1911 participants). Overall, findings were inconsistent and the majority of trials demonstrated high risk of bias. Interventions were predominantly delivered to women during pregnancy and only two studies included fathers. There was some evidence that adapting interventions to the pre and postnatal periods provided benefits for stress and anxiety reduction, however there was limited evidence for individual intervention types or approaches. Conclusions: There is currently inconsistent evidence of what interventions are most effective for women during the first 1000 days and there is insufficient evidence for any interventions for male partners during this period. There is a clear need for rigorous development and examination of interventions developed specifically to reduce or prevent stress and/or anxiety across the first 1000 days.
PUBLISHED
Keywords: Stress; Anxiety; Interventions; Prenatal; Postpartum